Evaluation of Nonviral piggyBac and lentiviral Vector in Functions of CD19chimeric Antigen Receptor T Cells and Their Antitumor Activity for CD19+ Tumor Cells - Lin, Zhicai; Liu, Xiangzhen; Liu, Tao; Gao, Haixia; Wang, Sitong; Zhu, Xingli; Rong, Lijie; Cheng, Jingbo; Cai, Zhigang; Xu, Fu; Tan, Xue; Lv, Linjie; et al. (Frontiers in Immunology, 2022)
Non-viral transposon piggyBac (PB) and lentiviral (LV) vector have been used to deliver chimeric antigen receptor (CAR) into T cells. To understand the differences of PB with LV in functions of CAR T cells, we constructed CAR to targeting CD19 with PB or LV vectors, delivered pbCAR or lvCAR into T cells and generated CD19pbCAR T or CD19lvCAR T cells. The results showed that both of CD19CAR T cells had strong cytotoxicity and increase of IFN-γ levels when incubating with Raji cells. TNF-α increased in CD19pbCAR T cells, while IL-10 increased in CD19lvCAR T cells. CD19pbCAR T cells showed the similar strong anti-tumor activity as CD19lvCAR T cells in Raji cell-induced mouse models and had slight decreased effect on mouse weight but increased the murine survival. Subsequently, the CD19pbCAR T cells demonstrated significant inhibition of Raji cell-induced tumor in vivo with the high concentration but not the low and middle one. The CD19pbCAR T cells in vivo distributed mostly in mesenteric lymphonodes, bone marrow of femur, spleen, kidney and lung, exhibiting specific accumulation at CD19-rich site or tumor location and increased CAR copy number at day 7. These results demonstrate that pbCAR has its own properties in activities and functions of pbCAR T cells, which makes it a valuable tool for CAR T immunotherapy.